Acromiocervical Flap As One of the Modality To Reconstruct Post-Burn Neck Contracture: A Case Report - Irwansyah, Denny; Sandhi, Afriyanti; Heryadi, Eko; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Abstract: Postburn neck contractures are frequent and may cause gross facial deformity and severe functional disability. Reconstruction of these deformities is challenging, especially to plastic surgeon. Several methods have been published including skin graft, local flap and free flap. Patient and Method: The case presented in this paper is a postburn neck contracture which had been managed by two plastic surgeons in two different hospitals. This deformity limits the normal function of eating, speaking and appearance of this patient. Skin graft was used to correct this deformity but in the next few months neck contracture recurred. Result: It results in minimal disability and in overall improved functional and appearance outcome. We report our experience using the acromiocervical flap on a case for reconstruction of neck contracture with a goal to prevent recurrence.Summary: Skin Grafting is not an easy and simple procedure for reconstruction of the neck contracture. It requires comprehensive rehabilitation program including prolonged neck splinting and patient compliance. Considering those difFIculties acromiocervical flap can be one of the modality to reconstruct post burn neck contracture because it is relatively simple and reliable.